Association of interest, attitude and learning habit in mathematics learning towards enhancing students’ achievement - Hashim, Suhaizal; Masek, Alias; Mohd Mahthir, Bismi Nurnazatul Shima; A. Rashid, Ana Haziqah; Nincarean, Danakorn (2021)
Mathematics is fundamentally important for Science and Technology, as well as in engineering. Mathematics is compulsory for students since all engineering subjects were Mathematically oriented. However, the preliminary study found that students’ achievement in Mathematics courses have been associated with three main factors, namely interest, attitude and learning habit, as in the KASH Model (Knowledge, Attitude, Skills and Habits). This Model stipulated that poor performance is not just lacking in knowledge and skills but also including poor attitude and habits. Therefore, this study aims to investigate the students’ level and relationship between interest, attitude and learning habit based on KASH Model. A total of 58 students were selected as a sample of the study, who enrolled in the Thermodynamics, Fluid Mechanics and Solid Mechanics subjects. A set of questionnaires with 21 items was used to collect data; a descriptively analysis was used to find the mean and percentage, as well as correlation index using Pearson. The results; high level of factor of interest, attitude and learning habit, and high correlation between interest, attitude and habit. The implication is that teaching and learning process must equally fostering all these variables to achieve a high level of students’ achievement, especially in Mathematics subjects.